Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4028/www.scientific.net/amr.150-151.852
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Antibacterial Activity of Copper-Carried Zirconium Phosphates

Abstract: Copper-carried zirconium phosphates (CuZrPs) were prepared by introducing copper ions into sodium zirconium phosphate (ZrP) through an ion-exchange method, and characterized by energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). The antibacterial activity and water resistance of CuZrPs were also investigated. The research results indicated that CuZrP-3 containing 10.86 mass% of copper exhibited excellent antibacterial activity and water resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Although the major product was BzH, benzoic acid was also formed as a side product ( Table 2, entries 4,5,8,11,14,15). It was found that by changing the reaction parameters such as time ( [12][13][14][15], the selectivity and/or yield were changed.…”
Section: Oxidation Reaction and Expected Mechanismmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the major product was BzH, benzoic acid was also formed as a side product ( Table 2, entries 4,5,8,11,14,15). It was found that by changing the reaction parameters such as time ( [12][13][14][15], the selectivity and/or yield were changed.…”
Section: Oxidation Reaction and Expected Mechanismmentioning
confidence: 96%
“…, or Ce 3? [5,[12][13][14]. There have also been several reports concerning the catalytic activities of ion-exchanged materials of this type, including the use of zinc zirconium phosphate (ZPZn) and copper zirconium phosphate (ZPCu) as catalysts in the acetylation of alcohols and phenols and the use of potassium iron zirconium phosphate as a catalysts in Friedel-Crafts benzoylation reaction [9,[18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 ZP behaves as a unique ion exchanger because of its exceptionally poor aqueous solubility, high thermal stability, resistance to radiation and abrasive properties. 4,5 The H + of the P-OH moiety in ZP can be exchanged for various other ions, which results in the enlargement of the interlayer distance. [6][7][8] Several studies pertaining to the successful exchange of the H + of the P-OH group in ZP with various divalent and trivalent cations have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Furthermore, ZP has been reported to exhibit antibacterial activity when it was loaded with Cu 2+ , Zn 2+ , or Ce 3+ . 5,[12][13][14] Several reports have also appeared in the literature concerning the catalytic activities of ion exchanged materials of this type, including the use of copper zirconium phosphate (ZPCu) as catalyst in the acetylation of alcohols and phenols and the use of zirconium phosphate-ferric chloride complex and potassium iron zirconium phosphate as catalyst in Friedel-Crafts reaction. [18][19][20][21][22][23][24] The selective oxidation of alcohols into the corresponding carbonyl compounds is an important research field since the corresponding aldehyde, ketone or carboxylic derivatives serve as important and versatile intermediates for the synthesis of various chemicals, vitamins, drugs and fragrances.…”
Section: Introductionmentioning
confidence: 99%